Evaluation of the efficacy of Abelmoschus manihot (L.) on diabetic nephropathy by analyzing biomarkers in the glomeruli and proximal and distal convoluted tubules of the kidneys - Hongmei Yu; Mei Wang; Jingshi Yu; Haitao Tang; Qing Xu; Ning Cheng; Xiaoxiao Luo; Yurong Wang; Haitao Ge; Lei Qiang; Wei Tang; Harvest F. Gu (Frontiers in Pharmacology, 2023)
Introduction: As a traditional Chinese medicine, Abelmoschus manihot (L.) in the form of Huangkui (HK) capsule has been used as a medication for kidney diseases, including diabetic nephropathy (DN), in China. The most significant effect of HK capsule treatment in kidney diseases is the reduction of albuminuria and proteinuria. To evaluate the efficacy of HK capsule in the regression of DN, in the current study, we analyzed the biomarkers in the glomerulus and proximal and distal convoluted tubules in the kidneys of db/db mice, the animal model for type 2 diabetes and DN.Methods: Huangkui capsules (0.84 g/kg/d) or vehicle were administered daily via oral gavage for 4 weeks in db/db mice. Urinary albumin-to-creatinine ratio and blood glucose levels were measured during the whole experimental period. Five biomarkers in the glomerulus and proximal and distal convoluted tubules in the kidneys were selected, namely, col4a3, slc5a2, slc34a1, slc12a3, and slc4a1, and their activities at mRNA and protein levels before and after HK capsule treatment were analyzed by real-time RT–PCR and immunohistochemistry.Result and discussion: After HK capsule treatment for 4 weeks, the urinary albumin-to-creatinine ratio in db/db mice was found to be significantly decreased. The activities of col4a3, slc5a2, slc34a1, slc12a3, and slc4a1 in the kidneys were upregulated in db/db mice prior to the treatment but downregulated after HK capsule treatment. Further analyses of the fields of whole kidney tissue sections demonstrated that the number of nephrons in the kidneys of db/db mice with HK capsule treatment was higher than that in the kidneys of db/db mice without HK capsule treatment. Thereby, the current study provides experimental evidence confirming the medical efficacy of A. manihot in the reduction of albuminuria and proteinuria, suggesting that A. manihot may have pharmacological efficacy in the regression of the development of type 2 diabetes-DN.